Direct effect of pholyphenol‐rich plants, rooibos and ginkgo, on porcine ovarian cell functions1. Issue 2 (11th October 2017) - Štochmaľová, A.; Kádasi, A.; Alexa, R.; Bauer, M.; Harrath, A. H.; Sirotkin, A. V.
Summary: The polyphenol‐rich plants rooibos and ginkgo are widely used in folk medicine and in preparation of foods and drinks, but their effect on reproduction has not been properly studied yet. The aim of our in vitro experiments was to examine the possible direct effect of rooibos and ginkgo on the basic ovarian cell functions—proliferation, apoptosis and release of hormones progesterone (P4) and leptin (L). Porcine ovarian granulosa cells were cultured in the presence of rooibos or ginkgo extract (0, 1, 10 and 100 μg/ml of medium). The accumulation of markers of proliferation (PCNA and cyclin B1) and apoptosis (bax) and their mRNAs was analysed using immunocytochemistry and by reverse transcription—quantitative polymerase chain reaction (RT‐qPCR). Release of P4 and L was evaluated by radioimmunoassay. It was observed that rooibos or ginkgo addition was able to inhibit proliferation (down‐regulates PCNA, cyclin B1 and their mRNAs), to promote apoptosis (accumulation of bax) and to suppress both L and P4 release by ovarian cells. These data suggest a direct inhibitory (anti‐proliferative, pro‐apoptotic and hormone‐suppressing) effect of polyphenol‐containing plants rooibos and ginkgo on ovarian functions. The potential anti‐reproductive effect of these medical plants is to be taken into account by their consumption.